(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose: This study aimed to examine the influence of general strain factors on cyberbullying among university students in Kenya, with a focus on emotional distress, coping mechanisms, peer reinforcement, and reduced empathy. Methodology: A quantitative research design was employed, using a structured questionnaire to collect data from student leaders across 72 universities in Kenya. The data were analyzed using Pearson correlation and regression analysis to explore the relationships between general strain factors and cyberbullying behaviors. Findings: The study found a moderate positive correlation (r = .492, p < .001) between general strain factors and cyberbullying. Specific strain factors such as negative emotions and coping mechanisms (r = .453, p = .001), and peer reinforcement (r = .404, p = .003) were significantly associated with higher cyberbullying severity. However, reduced empathy showed a non-significant relationship (r = .214, p = .127). Regression analysis revealed that general strain factors explained 24.2% of the variance in cyberbullying (R² = .242, p < .001), confirming their significant predictive role. Unique Contribution to Theory, Practice, and Policy: The study offers a unique contribution to General Strain Theory (GST) by demonstrating how emotional distress and peer validation processes contribute to cyberbullying in the Kenyan university context. It also highlights the importance of addressing strain factors such as stress, isolation, and peer reinforcement in university policies and intervention strategies. The study suggests the incorporation of mental health programs, stress-management initiatives, and digital ethics training in universities to mitigate the risks associated with cyberbullying.